The Malaysian fatwa framework and its relevance to anti terrorism policy: a critical reflection on the Nigerian "Boko Haram" causes - Chiroma, Magaji; Ansari, Abdul Haseeb; Arifin, Mahamad; Abdullah, Mohamad Asmadi (2014)
"In some of the Modern Muslim and secular countries, the role" "of fatwa (Islamic legal verdict) has been understood and utilized as an instrument for social, political and religious control. This role has gone far as sustaining the peaceful co-existence and harmony among different people of different background. Fatwa institutions harmonize the religious perceptions, ideologies and believes of people, thereby regulating their conduct of religious activities in such a manner acceptable to the Islamic tenets and contemporary developments. In Malaysia, success has been tremendously recorded in the area of the administration of Islamic law: politically, legally, economically and religiously. From the perspective of the religion; Islamic organizations and institutions have been established and bureaucratized (including fatwa institutions), Mosques have been controlled and fine-tuned by the states' agencies, and the Islamic teachings and preaching have been also regulated to an extent that religious fundamentalism and evil ideologies in the country are restricted. It is based on admiring such practice that the paper makes a reflection on the causes of Boko Haram insurgency in Nigeria with a view to revealing the relevance of the Malaysian jatwa framework to Nigeria for preventing the future occurrence of the insurgency and terrorism in the country. To this end, the paper suggests among other things; that the Nigerian Government (including state Governments) in consultation with the Islamic scholars in the country, should immediately set up a powerful Islamic fatwa committee, or empower the existing fatwa bodies with statutory legal backing, thereby using Malaysia as a role model; that the Government should also intensifY its supervision on the activities of some of the Islamic organizations, International NGOs and non religious organizations in the country; and that the Government should set up some necessary machineries on ground for the purpose of making the above suggestions reality, such as the amendment of the 1999" "Nigerian Constitution and relevant legislation in the country."